2006
DOI: 10.1161/01.str.0000221786.81354.d6
|View full text |Cite
|
Sign up to set email alerts
|

Hematoma Growth and Outcome in Treated Neurocritical Care Patients With Intracerebral Hemorrhage Related to Oral Anticoagulant Therapy

Abstract: Background and Purpose-Intracerebral hemorrhage (ICH) is the most serious and potentially fatal complication of oral anticoagulant therapy (OAT). Still, there are no universally accepted treatment regimens for patients with OAT-ICH, and randomized controlled trials do not exist. The aim of the present study was to compare the acute treatment strategies of OAT-associated ICH using vitamin K (VAK), fresh frozen plasma (FFP), and prothrombin complex concentrates (PCCs) with regard to hematoma growth and outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(110 citation statements)
references
References 40 publications
2
104
2
2
Order By: Relevance
“…Several studies comparing the efficacy of PCCs with human plasma for emergency oral anticoagulant reversal have shown that PCCs provide more effective and more rapid correction of coagulopathy [44-47]. These findings, together with the improved safety profile of today's PCCs, suggest that PCCs should be considered preferable to FFP for emergency oral anticoagulant reversal.…”
Section: Comparing Pccs With Human Plasmamentioning
confidence: 99%
“…Several studies comparing the efficacy of PCCs with human plasma for emergency oral anticoagulant reversal have shown that PCCs provide more effective and more rapid correction of coagulopathy [44-47]. These findings, together with the improved safety profile of today's PCCs, suggest that PCCs should be considered preferable to FFP for emergency oral anticoagulant reversal.…”
Section: Comparing Pccs With Human Plasmamentioning
confidence: 99%
“…A recent German observational study on VKA‐OAC (n = 1,176), published after the submission of our study, suggested that rapid reversal of INR is associated with less ICH expansion and lower in‐hospital mortality, but was not powered to compare reversal therapies due to a uniform national practice of using PCC 24. Previous observational studies comparing treatments have been small (17–181 patients), with variable results with regard to case fatality,14, 25, 26 functional outcome,27, 28 and hematoma expansion 29. These studies also combined patients receiving FFP with either PCC26, 29 or no reversal,14, 23, 27 precluding direct comparison of specific reversal strategies.…”
Section: Discussionmentioning
confidence: 97%
“…Previous observational studies comparing treatments have been small (17–181 patients), with variable results with regard to case fatality,14, 25, 26 functional outcome,27, 28 and hematoma expansion 29. These studies also combined patients receiving FFP with either PCC26, 29 or no reversal,14, 23, 27 precluding direct comparison of specific reversal strategies.…”
Section: Discussionmentioning
confidence: 99%
“…3,41,42 While the correction of the INR is a surrogate outcome, there is some, albeit limited, data to suggest that PCC may reverse the anticoagulation more rapidly and, therefore, the bleeding associated with VKA toxicity. In a retrospective single centre study, the use of PCC alone or in combination with vitamin K was associated with a reduced incidence and extent of ICH hematoma growth compared with FP alone or in combination with vitamin K. 43 While this study included a small population (n = 55), an association between early (i.e., within two hours) normalization of INR and the prevention of hematoma growth in both the FP-and PCC-treated groups supports the use of INR as an outcome to compare the efficacy of these treatment options.…”
Section: Dosage and Efficacymentioning
confidence: 94%